Juridical Review of Submission of Waqf Land by Foreign Dwellers in Indonesia - Onny Medaline (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
In the legal provisions in Indonesia, waqf is defined as a legal act of a person or legal entity that separates a portion of his property in the form of land belonging and institutionalizes the interests of worship or other public purposes in accordance with the teachings of Islam. From this definition, it is not mentioned about waqf limitation in the handover of waqf, both Indonesian citizens and foreigners who reside in Indonesia. The study on the granting of waqf land by foreigners residing in Indonesia can be seen from several different points of view, ie, both from the population administration law, from the various regulations governing the residence of foreigners residing in Indonesia, and from legal review of waqf that exist in Indonesia. On the basis of UUPA and regulations concerning the administration of residence for foreigners, foreigners with a land tenure with Right to Use may be located as waqif. Since the right to use is a right to participate on the land of the right of the State, or land of management rights, or land of property rights, then with the expiration of the term of tenure, will result in the expiry of the expiration of waqf land use.